2014
DOI: 10.1111/aas.12264
|View full text |Cite
|
Sign up to set email alerts
|

Recovery after nasal surgery vs. tonsillectomy: discriminant validation of the Postoperative Quality of Recovery Scale

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Background: Initial validation and feasibility of the PostOperative Quality of Recovery Scale (PQRS) was published in 2010. Ongoing validation includes studies to determine whether this scale can discriminate differences in recovery in similar patients having different surgery. Methods: A prospective observational study included 89 patients undergoing nasal surgery and 46 patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…[45] Certain items (such as the emotive domain) typically show high early recovery, which remained that way, whereas nociception and cognition tend to have a slower recovery profile over days to weeks. The findings of this study were consistent with prior studies conducted in English.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] Certain items (such as the emotive domain) typically show high early recovery, which remained that way, whereas nociception and cognition tend to have a slower recovery profile over days to weeks. The findings of this study were consistent with prior studies conducted in English.…”
Section: Discussionmentioning
confidence: 99%
“…In English version, face validity, feasibility, and discriminate validity have been shown, and it has been translated into eight languages. [34567] The background and use of the scale have been described elsewhere,[3] including the recalibration of cognitive scoring. [6] The PostopQRS assess quality of recovery in five domains: physiological, emotive, nociceptive, functional (i.e., activities in daily living), and cognitive.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in subsequent validation of the Postoperative Quality of Recovery Scale, four studies were constructed to show the ability to discriminate recovery and cognition in different cohorts of participants (mixed cohort, orthopedics, and otolaryngology), as well as a human volunteer study to calibrate the cognitive domain. [46474849]…”
Section: Validating a Questionnairementioning
confidence: 99%
“…A subsequent feasibility study confirmed face validity , with a further volunteer study confirming performance variability, test reliability and validation of the telephone method of conducting the survey . The PQRS showed good discriminant validity, with a significant association between anaesthetic duration and recovery at different study time points over all six domains (p < 0.001) . Face validity was confirmed with improved patient recovery over time (0.3%, 1.7%, 5.9% and 12% at T15, T40, D1 and D3, respectively).…”
Section: Discussionmentioning
confidence: 60%
“…Discriminant validation using multiple trials, different surgical populations and time frames is a very important aspect that is seldom performed. The PQRS is undergoing discriminant validation, and is able to show group differences where expected with relatively small sample sizes . Additional validation criteria that are assessed include internal consistency, reproducibility, responsiveness, interpretability, and floor and ceiling effects.…”
Section: Discussionmentioning
confidence: 99%